Assessment of Nutritional Status and Food Behavior among Primary School Children in Erbil City - Jbraeil Sulaiman , Saad; Hashim AlAni , Mouroge (International Journal of Psychosocial Rehabilitation, 2020)
Background and objective: As a result of the prevalence of sedentary lifestyles, changes in food behavior, and urbanization, particularly in developing countries, there has been an increase in the prevalence of childhood obesity and overweight, which can cause numerous complications later in adult life. The present study was carried out in order to identify the obesity prevalence rate and its risk factors among primary school children in Erbil, the Kurdistan Region of Iraq. Patients and methods: The present cross-sectional descriptive study was carried out on 252 children aged 6-13 years chosen from primary schools in Erbil from 2017 to 2019. Required sociodemographic and socioeconomic data were collected using a researcher-designed questionnaire through face-to-face interviews with the children’s parents. The children’s weight was measured using a UNICEF-calibrated digital scale, their height through a portable stadiometer, and their body mass index based on their height and weight. The collected data were analyzed using suitable tests through Statistical Package for the Social Sciences (version 22). Results: The female-to-male ratio was 1.15:1. Most of the students (73.4%) had been breastfed for 7 or more months. Most of them (62.3%) did not have a family history of obesity. Of them, 42.9% were found to be obese and 17.5% were overweight. Their nutritional status was found to be significantly correlated with their food habits, age, grade, maternal occupation, family history of obesity, daily pocket money, breastfeeding duration, and socioeconomic status (p<0.05). However, there was no significant association between their nutritional status and gender, parents’ marital status, father’s occupation, and parents’ educational level (p > 0.05). Conclusion: Food habits, age, grade, maternal occupation, family history of obesity, daily pocket money, breastfeeding duration, and socioeconomic status are among risk factors for childhood obesity/overweight. Therefore, children with such risk factors are recommended to be taken into special consideration in order to prevent their probable obesity/overweight early.